Analisis Maturitas Kesehatan Digital pada Klinik di Kabupaten Ponorogo - Noor, Muhammad Syeikhooni; Heryawan, Lukman; Sanjaya, Guardian Yoki (Politeknik Negeri Jember, 2026)
Digital transformation in primary healthcare services plays a crucial role in supporting the national SATUSEHAT integration initiative. This study aims to measure digital maturity levels and analyze their determining factors within the clinic ecosystem in Ponorogo Regency. A quantitative approach was applied using a census sampling technique involving all 43 clinics as respondents. The findings indicate that the average digital maturity level falls into the “High” category, with a mean score of 4.03 out of 5.00. Among the assessed dimensions, Governance and Leadership emerged as the strongest, while Interoperability was identified as the weakest. Statistical analysis revealed a significant positive correlation between digital maturity scores and the intensity of data submission to the SATUSEHAT platform (p-value = 0.021). The results suggest that the current digital maturity profile is primarily driven by regulatory compliance rather than organic technical development, with managerial readiness exceeding infrastructure capability. Strategic recommendations propose that clinics prioritize investments in meeting interoperability standards. Additionally, local Health Offices should shift their role from administrative oversight to technical facilitation to address challenges within the electronic medical record vendor ecosystem and support sustainable digital integration in primary healthcare services.